The Jurisdiction of the Prosecutor's Office is to Confiscate Assets and Eradicate the Crime of Money Laundering - Santoso, Prijo; Pujiono, Bambang (Jurnal Multidisiplin Madani, 2024)
Simply put, money laundering is the criminal act of transforming the proceeds of crimes, or what is known as "dirty money," such as money obtained through smuggling, gambling, tax evasion, drug sales, or corruption, into a form that seems safe and legal for use. Both a conceptual and legislative approach are used in this normative research. Legal approach by examining Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes and Law Number 8 of 2010 concerning Eradication of Money Laundering Crimes. The practice of seizing property used in illicit conduct with the goal of returning it is known as asset confiscation. The meaning of the term confiscation is connected to confiscation which is commonly used in the asset confiscation system for the purpose of returning asset recovery as used in UNCAC 2003